(untitled) (Research, Society and Development, 2020)
Objectives: To identify the types of congenital heart diseases among newborns in the year 2016. Methods: A retrospective, quantitative and descriptive study was carried out based on the evaluation of medical records. The medical records of the patients who underwent transthoracic echocardiography performed in 2016 were analyzed on the type of heart disease, birth weight, gestational age, gender, and clinical outcome of newborns in the maternity ward in Santa Catarina State, from 0 to 28 days old. Results: Transthoracic echocardiograms revealed atrial septal defect, persistent ductus arteriosus, ventricular septal defect, transposition of large vessels at baseline, atrioventricular septal defect, tricuspid insufficiency, and coarctation of the aorta in descending order. The incidence of congenital heart disease in the sample collected was 14:1000. Prevalent gestational age was preterm, most of them with adequate weight for gestational age with low weight. Clinical outcome was hospital discharge in most cases. Conclusions: The profile of the cardiopathies, the predominance of low weight and the precocious gestational age point to the need for early diagnosis in order to avoid late repercussions that could be avoided through clinical follow - up and surgical interventions when necessary. The research points out the importance of the active search for congenital heart diseases in the neonatal period, suggesting the use of the fetal echocardiogram as an integral prenatal examination recommended by the Unified Health System, starting at 30 weeks of gestation.